2018
DOI: 10.15835/nsb10210187
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Agronomic Responses of Four Rice Varieties to Drought in the Rainforest

Abstract: The present investigation tested the hypothesis that there would be variation in physiological responses to water deficit among rice varieties from different production ecologies, with contrasting tolerance to water deficit under repeated cycle of soil moisture deficit, at reproductive growth stage. A screen house and a field trial were conducted at International Institute of Tropical Agriculture, Ibadan and Ikenne (Latitude 6° 52' N, Longitude 3° 43' E) respectively. Both experiments had rice varieties (‘IR 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…To conclude from both these fields and the previous biotron (Mukamuhirwa et al, ) studies, severe drought conditions during early plant development impacted panicle development, thus affecting grain yield, whereas drought at the reproductive stage results in a stronger impact on spikelet fertility. Also, previous research has shown impact of drought on spikelet sterility, thereby affecting grain yield (Fofana et al, ; Moonmoon & Islam, ). The results of the present study indicate spikelet fertility and weight of 100 grains as important grain yield components having an impact on total grain yield.…”
Section: Discussionmentioning
confidence: 96%
“…To conclude from both these fields and the previous biotron (Mukamuhirwa et al, ) studies, severe drought conditions during early plant development impacted panicle development, thus affecting grain yield, whereas drought at the reproductive stage results in a stronger impact on spikelet fertility. Also, previous research has shown impact of drought on spikelet sterility, thereby affecting grain yield (Fofana et al, ; Moonmoon & Islam, ). The results of the present study indicate spikelet fertility and weight of 100 grains as important grain yield components having an impact on total grain yield.…”
Section: Discussionmentioning
confidence: 96%
“…The start of breeding for interspecific (NERICA) varieties between Oryza sativa and Oryza glaberrima was in 1992 (Jones et al 1997) and the first release of NERICA varieties was in 2002 in Côte d'Ivoire and Guinea. All upland NERICA varieties possess short growth duration and comparable yield with improved upland varieties (Somado et al 2008) and have the respective advantages such as NERICA 4 with drought tolerance (Fofana et al 2018), which has become popular in SSA especially in Uganda because of the drought tolerance (Britwum et al 2020). In addition to the numbered NERICA varieties-i.e.…”
Section: Reviewmentioning
confidence: 99%